(3JShjb GdUGOQGJ GdYQHjI (B:s (3BdjGJ JaYjd GdJShjb GdOhdj hefGWb GdJLGQI GdMQI GdYQHjI GdcHQi (B/s - (3GdfLGQ, aQjOs ((3GdbGgQI(B: s (3OGQ bHGA ddWHGYI hGdfTQ hGdJhRjY(B, s, 2002)
(3GdMQhH GdJLGQjI hGdJShjb GdOhdj(B-(3GTcGdjI GdJUOjQ GdYQHj(B-(3GdYhdeI hJMOjGJ GdJUOjQ(B-(3GdEWGQ GdYGe dJShjb GdUGOQGJ(B-(3GdJfGaSjI GdOhdjI hehba GdUGOQGJ(B-(3GdEOGQI GdGSJQGJjLjI ddJShjb GdJUOjQj(B-(3GYOGO GdHQGeL GdeJcGedI ddJUOjQ(B-(3GJaGbjGJ GdJeKjd GdJLGQj hMSe GdefGRYGJ GdJUOjQjI(B-(3HMhK GdJShjb GdOhdj hGdUGOQGJ(B-(3JMOjO GdehGUaGJ GdfeWjI ddUGOQGJ(B-(3Sdhc GdeSJgdc GdOhdj(B-(3Jehjd GdUGOQGJs
(3HHdhZQGajG U(B.389s
Keywords: (3GdJShjb GdOhdjs; (3GdJUOjQs; (3GdYhdeIs